Technical efficiency and its convergence among village clinics in rural China: evidence from Shanxi Province - Ye, Yun; Evans, Richard; Huang, Xiaojun; Xu, Wei; Lu, Wei (Frontiers in Public Health, 2024)
Village clinics (VCs) are the foundation of the three-tiered health service system in China, delivering basic and routine outpatient services to citizens in rural China. VC technical efficiency and its convergence play a critical role in policy decisions regarding the distribution of health service resources in rural China. This study measured VC technical efficiency (using the slacks-based measure model), its convergence (using the convergence model), and the factors that influence the convergence in Shanxi Province, China. Data were obtained from the Shanxi Rural Health Institute 2014-2018 Health Statistics Report, which involved 3,543 VCs. The results showed that VC technical efficiency was low and differed by region. There was no convergence in VC technical efficiency, but evidence of  convergence was found in Shanxi. The main factors that influence convergence were the building area of each VC (BA), proportion of government subsidies (PGS), and ratio of total expenditure to total income of each VC (RTETI).